Primary Human Lymphocytes Transduced with NY-ESO-1 Antigen-Specific TCR Genes Recognize and Kill Diverse Human Tumor Cell Lines - Zhao, Yangbing (2005)
cDNAs encoding TCR α- and β-chains specific for HLA-A2-restricted cancer-testis Ag NY-ESO-1 were cloned using a 5′RACE method from RNA isolated from a CTL generated by in vitro stimulation of PBMC with modified NY-ESO-1-specific peptide (p157–165, 9V). Functionality of the cloned TCR was confirmed by RNA electroporation of primary PBL. cDNA for these α- and β-chains were used to construct a murine stem cell virus-based retroviral vector, and high titer packaging cell lines were generated. Gene transfer efficiency in primary T lymphocytes of up to 60% was obtained without selection using a method of precoating retroviral vectors onto culture plates. Both CD4(+) and CD8(+) T cells could be transduced at the same efficiency. High avidity Ag recognition was demonstrated by coculture of transduced lymphocytes with target cells pulsed with low levels of peptide (<20 pM). TCR-transduced CD4 T cells, when cocultured with NY-ESO-1 peptide pulsed T2 cells, could produce IFN-γ, GM-CSF, IL-4, and IL-10, suggesting CD8-independent, HLA-A2-restricted TCR activation. The transduced lymphocytes could efficiently recognize and kill HLA-A2- and NY-ESO-1-positive melanoma cell lines in a 4-h (51)Cr release assay. Finally, transduced T cells could efficiently recognize NY-ESO-1-positive nonmelanoma tumor cell lines. These results strongly support the idea that redirection of normal T cell specificity by TCR gene transfer can have potential applications in tumor adoptive immunotherapy.